Comparison of direct and indirect images and hemodynamic response of two different video laryngoscopes to tracheal intubation - Özlem Sezen; Tahsin Şimşek; Aynur Kaynar Şimşek; Gülten Arslan; Kemal Tolga Saracoglu; Ayten Saracoglu (BMC Anesthesiology, 2025)
Abstract Aims The aim of this study was to compare the effects of two different videolaryngoscopes (VLs) on direct (through the mouth) and indirect (screen images) laryngoscopy and to evaluate their effects on hemodynamic response. Settings and design A total of 70 patients between the ages of 18 and 65 years with ASA I-III physical status, planned for general anesthesia, with an expected difficult airway, were included in the study. Patients were enrolled in the study between 02/ 2022 and 06/ 2022. Patients were randomly divided into two groups. McGrath video laryngoscope was used in Group MC and Hugemed video laryngoscope was used in Group H. Modified Cormack Lehane and POGO scores (Percentage of glottic opening) of all patients on direct and indirect laryngoscopy were evaluated and recorded and then orotracheal intubation was performed. Demographic data, ASA status, Mallampati classification, thyromental distances and mouth opening were recorded. Standard monitoring was applied to all patients. During intubation, endotracheal intubation time, number of attempts, intubation-related complications and sore throat were recorded. Hemodynamic parameters (mean arterial pressure, peripheral oxygen saturation values) were recorded before, after induction and after intubation. Results There was no difference between the groups in terms of descriptive characteristics (p > 0.05). When direct and indirect POGO scores were compared in group MC, no difference was found between the patients (p > 0.05). When direct and indirect POGO scores were compared, no difference was found between patients in Group H (p > 0.05). The mean POGO VL indirect score of Group H patients was found to be significantly higher than that of Group MC (p < 0.035) Both VLs showed similar results in terms of intubation time, number of attempts and hemodynamic findings. Conclusions McGrath and Hugemed videolaryngoscopes provide a good laryngeal view with similar Cormack Lehane scores during non-difficult endotracheal intubation and facilitate successful intubation by maintaining hemodynamic stability. It was observed that the Hugemed VL had a better indirect POGO score, but the images provided by the blades of both VLs on direct laryngoscopy allowed intubation. Clinical Trials Registration Number NCT06649526. Clinical trials registration date 17/10/2024 ‘’retrospectively registered’”.